2013
DOI: 10.1007/s10902-013-9458-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Employee Mental Health: The Relationship Between Intrinsic Need Satisfaction, Job Crafting, and Employee Well-Being

Abstract: Organisations are frequently confronted with the issue of how to enhance employee mental health. Based on Self-Determination Theory, a model is proposed that examines the relationships between job crafting, the satisfaction of the intrinsic needs for autonomy, competence, and relatedness at work, and employee well-beingdefined here as both subjective well-being and psychological well-being. A sample of 253 working adults completed a battery of questionnaires including the job JOB CRAFTING, NEED SATISFACTION, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(192 citation statements)
references
References 71 publications
(84 reference statements)
10
148
0
7
Order By: Relevance
“…Consistent with studies finding that both autonomy support and job crafting are related to well-being (e.g., Deci et al 2001;Gagné and Deci 2005;Moreau and Mageau 2012;Nielsen and Abildgaard 2012;Petrou et al 2012;Slemp and Vella-Brodrick 2014;Tims et al 2012Tims et al , 2013a, the current study also found that both factors independently predicted workplace well-being. However, there was also some suggestion of a synergistic relationship between autonomy support and job crafting, such that employees with the greatest positive affect both perceived their managers as the most autonomy supportive, and engaged in the highest amounts of job crafting.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with studies finding that both autonomy support and job crafting are related to well-being (e.g., Deci et al 2001;Gagné and Deci 2005;Moreau and Mageau 2012;Nielsen and Abildgaard 2012;Petrou et al 2012;Slemp and Vella-Brodrick 2014;Tims et al 2012Tims et al , 2013a, the current study also found that both factors independently predicted workplace well-being. However, there was also some suggestion of a synergistic relationship between autonomy support and job crafting, such that employees with the greatest positive affect both perceived their managers as the most autonomy supportive, and engaged in the highest amounts of job crafting.…”
Section: Discussionsupporting
confidence: 90%
“…Through job crafting, employees can tailor their existing jobs to more closely align with their needs, values, and skill sets, producing a more internalized motivation for their work and thus creating a more enjoyable, engaging, and meaningful experience on the job (Berg et al 2010;Wrzesniewski 2003;Wrzesniewski and Dutton 2001). This theoretical model was supported recently by Slemp and Vella-Brodrick (2014) who, using structural equation modeling (SEM), found that job crafting predicted psychological need satisfaction at work, which in turn predicted well-being. These findings suggest that job crafting may provide employees with an important avenue for enhancing their workplace well-being through the satisfaction of psychological needs.…”
Section: Individual Behavior and Employee Well-being: The Role Of Jobmentioning
confidence: 70%
See 1 more Smart Citation
“…Slemp e Vella-Brodrick (2014) corroboraram evidências para o fato de que o job crafting pode ser uma base fundamental para as intervenções sobre o bem-estar dos trabalhadores. Usando métodos de modelagem de equações estruturais, determinou-se que o job crafting é um preditor da satisfação das necessidades intrínsecas, que por sua vez são preditoras do bem-estar do trabalhador (Slemp & Vella-Brodrick, 2014).…”
Section: Instrumentounclassified
“…According to the theory of self-determination, employees have a demand of self-management. When employees feel their works are in control, they will show higher organizational commitment, and experience the happiness (Slemp & Vella-Brodrick, 2014). Based on the analysis, leader group prototypicality having a positive relationship with team commitment, and team commitment can improve employee well-being.…”
Section: Group Commitment As a Mediator Of Leader Group Prototypicalimentioning
confidence: 99%